Enhanced radiation tolerance in immiscible Cu/Fe multilayers with coherent and incoherent layer interfaces. Issue 9 (17th February 2015) - Chen, Youxing; Fu, Engang; Yu, Kaiyuan; Song, Miao; Liu, Yue; Wang, Yongqiang; Wang, Haiyan; Zhang, Xinghang
Abstract: Abstract : Recent studies have shown that chemical immiscibility is important to achieve enhanced radiation tolerance in metallic multilayers as immiscible layer interfaces are more stable against radiation induced mixing than miscible interfaces. However, as most of these immiscible systems have incoherent interfaces, the influence of coherency on radiation resistance of immiscible systems remains poorly understood. Here, we report on radiation response of immiscible Cu/Fe multilayers, with individual layer thickness h varying from 0.75 to 100 nm, subjected to He ion irradiation. When interface is incoherent, the peak bubble density decreases with decreasing h and reaches a minimum when h is 5 nm. At even smaller h when interface is increasingly coherent, the peak bubble density increases again. However, void swelling in coherent multilayers with smaller h remains less than those in incoherent multilayers. Our study suggests that the coherent immiscible interface is also effective to alleviate radiation induced damage.